E-government and e-services in local government: A case study - Bayona-Oré, Sussy (2021)
E-government requires the intensive use of ICTs (information and communication technologies) in public institutions to deliver services to citizens efficiently and effectively. E-government allows the transformation of the citizen service delivery system, and its implementation is conditioned by a set of critical factors. The city halls are directly connected with citizens and deliver e-services, but the importance of this level of government is sometimes underestimated. This study aims to explore the influence of critical factors on the eservices implementation in city halls. The authors used a model to assess the e-government development index of 10 city halls and to know the provision of e-services of city halls. The results reveal that the city halls in the study currently offer e-services at the levels of presence and urban information. It important that the efforts of city halls must be oriented to the levels of interaction, transaction and e-democracy. © 2021, World Scientific and Engineering Academy and Society. All rights reserved.